An analysis of different types of interstate certificates of veterinary inspection - Holmes, Taylor (My University, 2019)
The ability to trace animals is important in the livestock industry especially when it comes to controlling and eradicating animal diseases. Since livestock production is such a large and economically important industry in Kansas, it becomes even more critical to protet that industry by controlling animal diseases. By having a strong traceability system in place, export markets experience growth because trade partners are confident in the quality of the livestock and livestock by products they would trade for. Interstate Certificates of Veterinary Inspection aid in the mission of being able to trace animals as animal movements occur. The overarching goal of this thesis is to compare and contrast the benefits and costs associated with the different types of Interstate Certificates of Veterinary Inspection (ICVI): paper, electronic CVIs (eCVIs) offered through each state’s department of agriculture, mobile ICVIs/AgView, GlobalVetLINK, Veterinary Services Process Streamlining, which is offered through USDA, and Vet Sentry. Information about background, features and costs of each type of ICVI will be discussed in detail. The trends of electronic versions of ICVIs being used for import of livestock into Kansas are compared to how many paper ICVIs are still being submitted for imports. Headcounts of livestock, bovine (beef and dairy), bison, ovine, caprine, equine, porcine, poultry, and cervid, being imported into the state of Kansas are analyzed. Additionally, the time in process and processing times of ICVIs are determined for each type of ICVI that the Kansas Department of Agriculture (KDA) receives. These data suggest that the majority of ICVIs are submitted through paper means, but that there is an increasing trend towards utilization of electronic versions. Processing times of ICVIs submitted electronically are significantly less than those of paper versions. Especially in cases of numerous cattle that need to be individually identified, it proved to shorten the data entry time largely with the use of electronic ICVIs. This analysis should serve as a basis for a move towards all ICVIs being submitted electronically to lessen the time it takes to respond to an emergency in which livestock movements need to be trace
Keywords: Interstate Certificate of Veterinary Inspection; Traceability; Animal movement; Veterinarian; Animal Health; ICVI